Doppler Echocardiographic Hemodynamic Changes Following Percutaneous Balloon Mitral Valvotomy - Gaffar, Mohammad Abdul; Ferdous, Jannatul; Suchi, Sharmin Shahnaz (Journal of Rangpur Medical College, 2026)
Background: Rheumatic mitral stenosis is a major cardiovascular burden in poorer nations, causing increasing hemodynamic compromise. Percutaneous balloon mitral valvotomy (PBMV) has emerged as the preferred treatment for symptomatic mitral stenosis with a healthy valve shape. Objective: This study aimed to assess the doppler echocardiographic hemodynamic changes following PBMV in individuals with rheumatic mitral stenosis. Methods: This prospective observational analysis comprised 24 patients with severe rheumatic mitral stenosis who received PBMV between January and July 2021 at the National Institute of Cardiovascular Diseases in Dhaka, Bangladesh. Patients aged 21-50 years with a Wilkins score ≤10 were enrolled. Transthoracic doppler echocardiography was performed 24 hours before and 24-48 hours after PBMV to measure peak transmitral pressure gradient, mean transmitral pressure gradient, and pulmonary artery systolic pressure. A paired Student's t-test was used for statistical analysis, with a significance level of p≤0.05. Results: The study cohort was largely female (70.8%), with a mean age range of 21-50 years. All patients complained of shortness of breath, and additional prevalent symptoms included palpitation (87.5%) and paroxysmal nocturnal dyspnea (83.33%). After PBMV, peak transmitral pressure gradient decreased from 18.04±5.23 mmHg to 12.42±5.87 mmHg (31.2% reduction, p=0.0001), mean transmitral pressure gradient decreased from 10.75±3.15 mmHg to 7.04±4.53 mmHg (34.5% reduction, p=0.0001), and pulmonary artery systolic pressure decreased from 33.50±17.41 mmHg to 25.63±13.83 mmHg (23.5% reduction, p=0.003). Conclusion: In individuals with rheumatic mitral stenosis, PBMV immediately improves doppler hemodynamic parameters such as transmitral pressure gradients and pulmonary artery pressure. These data show PBMV's efficacy in improving hemodynamic outcomes and support its use as the recommended strategy for appropriate patients with mitral stenosis. J Rang Med Col.2026 Mar;11(1): 63-68